Estudio fitoquímico de los extractos de baja y mediana polaridad de Aristolochia mycteria - Prado Villanueva, Luis (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
From the Aristolochia mycteria, we obtained its hexane and dichloromethane extracts, isolating six secondary metabolites. About the hexane extract, 2 neolignane-type metabolites were isolated licarin-A (52) and licarin-B (24), which have been attributed to antioxidant activity. Another metabolite that was isolated beta-caryophyllene epoxide (54), a sesquiterpene with different applications as an additive in the food industry. On the other hand, from the dichloromethane extract, the phytosterols stigmasterol (50) and beta-sitosterol51) were isolated, also evidencing the presence of neolignans in this extract in good yield and accompanied by another neolignan-type structure of this previously reported as eupomatenoid-7 (53). Another important point to highlight is that the correct stereochemical identification of compound 52 was achieved by X-ray diffraction. Using 52 and 24 as raw material, aldehydes 55 and 56 were synthesized by Vilsmeier-Haack reaction, which was used taking advantage of their reactivity to obtain derivatives 57 and 58 by reduction with NaBH4, monitoring the reactivity of the aldehydes. We prepared their respective Schiff bases by using hydroxylamine hydrochloride obtaining derivatives 60 and 61, in addition using 2,4-dinitrophenylhydrazine we obtained hydrazone 62. Finally, the ester 63 was carried out by evaluating different coupling reagents, by using cinnamates, the ester 65 was obtained with which the influence of functional groups in the Vilsmeier-Haack reaction was evaluated, thus obtaining derivative 66.

A partir de los tallos y hojas de Aristolochia mycteria se obtuvieron los extractos hexánicos y diclorometánicos de los cuales se logró el aislamiento de seis metabolitos secundarios. En lo respecta al extracto hexánico se aislaron tres metabolitos los cuales se identificaron con sus datos espectroscópicos correspondiendo para la licarina-A (52), licarina-B (24) y el epóxido de ?- cariofileno (54), del extracto diclorometánico se obtuvieron los fitoésteroles estigmasterol (50) y ?-sitosterol (51) además de los metabolitos neolignánicos en cantidades significativas, resaltando la presencia del eupomatenoide-7 (53) otro metabolito de tipo neolignánico aislado solamente de este extracto en esta planta. Utilizando 52 y 24 principalmente como materia prima, se sintetizaron mediante reacción de Vilsmeier-Haack los aldehídos 55 y 56 los cuales fueron utilizados para la obtención de los derivados 57 y 58 mediante reducción con NaBH4, dando seguimiento a la reactividad de los aldehídos se prepararon sus respectivas bases de Schiff mediante el empleo de clorohidrato de hidroxilamina obteniendo los derivados 60 y 61, además de también emplear 2,4- dinitrofenilhidrazina para la obtención de la hidrazona 62. Finalmente se logró la obtención del éster 63 mediante la evaluación de diferentes reactivos acoplantes, mediante el empleo de cinamatos se obtuvo el éster 65 con el cual se evaluó la influencia de los grupos funcionales en la reacción de Vilsmeier-Haack obteniendo así el derivado 66.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias Químicas
Keywords: info:eu-repo/classification/cti/2; IIQB-R-M-2022-0510; Neolignano; Vilsmeier-Haack; Aldehído; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6753